2018
DOI: 10.1063/1.5049334
|View full text |Cite
|
Sign up to set email alerts
|

Firing and gettering dependence of effective defect density in material exhibiting LeTID

Abstract: The investigation of LeTID effects in mc-Si material requires repeated measurements of the minority charge carrier lifetime eff. Due to the inhomogeneous nature of mc-Si, measurements of eff should be carried out in a spatially resolved way. In this work, we show results for the impact of firing and gettering on LeTID in high quality mc-Si material and analyse them in terms of the effective defect density Neff while retaining the spatial information. We show that especially for low peak firing temperature degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…These combined maps reveal homogenous LeTID in the good grain areas, with less degradation at the grain boundaries. Such LeTID distribution corresponds to previous LeTID studies of mc-Si PERC cells [5] and lifetime samples [6], [26]. The highest N * LeTID is measured at certain clusters of initially highly recombination-active extended defects, which has also been observed by Niewelt et al [6].…”
Section: A Direct Versus Remote Pecvdsupporting
confidence: 88%
“…These combined maps reveal homogenous LeTID in the good grain areas, with less degradation at the grain boundaries. Such LeTID distribution corresponds to previous LeTID studies of mc-Si PERC cells [5] and lifetime samples [6], [26]. The highest N * LeTID is measured at certain clusters of initially highly recombination-active extended defects, which has also been observed by Niewelt et al [6].…”
Section: A Direct Versus Remote Pecvdsupporting
confidence: 88%
“…Finally, Figure 3C reveals that the degradation is rather uniform laterally in good grain areas, which is characteristic of LeTID. 12,14 However, defect clusters show slightly stronger LeTID, as reported recently, 37,38 which is even more pronounced in the acidictextured cells (Figure 3E,F).…”
supporting
confidence: 84%
“…Recent studies suggest that P or Al‐gettering can suppress LeTID to some extent, especially in material with low lifetime . Zuschlag et al showed that P‐diffused SiN x ‐passivated mc‐Si lifetime samples experienced only slight degradation, whereas a stronger and faster LeTID was observed in ungettered sister samples .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…3. Since a mere decrease of the firing temperature does not erase the difference between LeTID in good grains and at grain boundaries [20], the weak LeTID in PERC B might be linked to the surface passivation deposition. …”
Section: Resultsmentioning
confidence: 99%